2021
DOI: 10.1111/jav.02734
|View full text |Cite
|
Sign up to set email alerts
|

Elevated phytohaemagglutinin‐induced skin‐swelling response at an intermediate number of MHC class II alleles in bluethroat nestlings

Abstract: Genes of the major histocompatibility complex (MHC) are crucial for adaptive immunity, and theory predicts that the optimal number of alleles is intermediate rather than maximal. Support for such an intermediate optimum in MHC allele count has mainly been demonstrated in studies on parasite load and reproductive traits. In this study we tested if an intermediate number of MHC class II (MHCII) alleles based on positively selected sites was correlated with an increased skin-swelling response to two consecutive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…More tests including male odor donors carrying a single MHC-II allele would have been needed to ascertain the quadratic nature of the relationship between male MHC-II diversity and the female's reaction to the odor sample. Recently, several studies in fish, snakes and birds have tested the "golden mean hypothesis" and have shown that individuals with intermediate MHC-diversity have higher reproductive success (Kalbe et al 2009), better immunity (Rekdal et al 2021) and lower parasite load (Wegner et al 2004;Madsen and Ujvari 2006). In kittiwakes, the optimum in MHC-II diversity has been tested in chicks only, and was found to be maximum in females (Pineaux et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More tests including male odor donors carrying a single MHC-II allele would have been needed to ascertain the quadratic nature of the relationship between male MHC-II diversity and the female's reaction to the odor sample. Recently, several studies in fish, snakes and birds have tested the "golden mean hypothesis" and have shown that individuals with intermediate MHC-diversity have higher reproductive success (Kalbe et al 2009), better immunity (Rekdal et al 2021) and lower parasite load (Wegner et al 2004;Madsen and Ujvari 2006). In kittiwakes, the optimum in MHC-II diversity has been tested in chicks only, and was found to be maximum in females (Pineaux et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanistic role of immune genotypes (TLR heterozygosity, MHC allele diversity, and specific alleles in both MHC and TLRs) in immune responses remains unclear. For example, while PHA is a T lymphocyte mitogen, and historically PHA response was thought to indicate T‐cell activation and proliferation (Strandin et al, 2018), timescales of typical PHA response assays do not allow for extensive T cell proliferation (Rekdal et al, 2021). PHA responses may represent a general increase in cytokine expression, inflammation and both innate and adaptive immune cell recruitment to the injection site (Martin II et al, 2006; Vinkler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%